Treatment of obstructive sleep apnea syndrome (OSAS) with mandibular advancement devices - a statement of the Portuguese society of pulmonology, the Portuguese society of stomatology and dental medicine, the Portuguese dental association, and the Portuguese society of temporomandibular disorders, orofacial pain and sleep - Sousa, Susana (2024)
With the purpose of establishing a consensus around clinical orientations for professionals involved in managing patients with sleep breathing disorders (SBD), an interdisciplinary group of scientific societies involved in this field discussed and reviewed all the published international guidelines from the American Dental Association, American Academy of Sleep Medicine, American Academy of Dental Sleep Medicine and the European counterparts. Treatment of SBD is multidisciplinary and should be made in concert with the patient, the sleep physician, and the qualified dentist to solve the individual, social, and economic burden of the disease,. This consensus document represents the current thinking of a team of Portuguese experts on managing patients with SBD based on the available evidence.